An Ultra-High-Energy Density Supercapacitor; Fabrication Based on Thiol-functionalized Graphene Oxide Scrolls - Rani, Janardhanan. R. (Nanomaterials (Basel), 2019)
Present state-of-the-art graphene-based electrodes for supercapacitors remain far from commercial requirements in terms of high energy density. The realization of high energy supercapacitor electrodes remains challenging, because graphene-based electrode materials are synthesized by the chemical modification of graphene. The modified graphene electrodes have lower electrical conductivity than ideal graphene, and limited electrochemically active surface areas due to restacking, which hinders the access of electrolyte ions, resulting in a low energy density. In order to solve the issue of restacking and low electrical conductivity, we introduce thiol-functionalized, nitrogen-doped, reduced graphene oxide scrolls as the electrode materials for an electric double-layer supercapacitor. The fabricated supercapacitor exhibits a very high energy/power density of 206 Wh/kg (59.74 Wh/L)/496 W/kg at a current density of 0.25 A/g, and a high power/energy density of 32 kW/kg (9.8 kW/L)/9.58 Wh/kg at a current density of 50 A/g; it also operates in a voltage range of 0~4 V with excellent cyclic stability of more than 20,000 cycles. By suitably combining the scroll-based electrode and electrolyte material, this study presents a strategy for electrode design for next-generation energy storage devices with high energy density without compromising the power density.